2006
DOI: 10.1073/pnas.0511011103
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 induces angiogenesis via a DCC-dependent ERK1/2-eNOS feed-forward mechanism

Abstract: Netrin-1 is critical for axonal pathfinding which shares similarities with formation of vascular network. Here we report that netrin-1 induction of angiogenesis is mediated by an increase in endothelial nitric oxide (NO ⅐ ) production, which occurs via a DCC-dependent, ERK1͞2-eNOS feed-forward mechanism. Exposure of mature aortic endothelial cells to netrin-1 resulted in a potent, dose-dependent increase in NO ⅐ production, detected by electron spin resonance. Scavenging NO ⅐ with 2-phenyl-4,4,5,5-tetramethyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(168 citation statements)
references
References 33 publications
9
156
0
3
Order By: Relevance
“…Angiogenic assay of mouse aortic discs was carried out as previously described (33). Briefly, aortas from siRNA-injected mice were harvested and cleaned of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Angiogenic assay of mouse aortic discs was carried out as previously described (33). Briefly, aortas from siRNA-injected mice were harvested and cleaned of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Newly-formed vessels induced by netrin-1 contain an intact EC monolayer surrounded by multiple cell layers. Nguyen et al [55] demonstrated that netrin-1 induces angiogenesis by increasing endothelial nitric oxide production via a DCC-dependent ERK1/2-eNOS feed-forward mechanism in aortic ECs. All these studies suggest that netrin-1 is a pro-angiogenic factor, albeit with some discrepancies (Table 1).…”
Section: Netrin-1 and Angiogenesismentioning
confidence: 99%
“…Stimulate EC Proliferation, migration, and TF [53] Independent of UNC5B, DCC, neogenin/--Increase endothelial NO production [55] DCC Promote vascular development [52] UNC5B/-----Facilitate focal angiogenesis in adult [54] ------Anti-angiogenic effect Block EC migration [27] UNC5B…”
Section: Effectsmentioning
confidence: 99%
“…Previous studies have found that netrin‐1 is present in the ECs of natural blood vessels and can promote angiogenesis through uncoordinated‐5 homolog B (UNC5B) and deleted in colorectal cancer (DCC) receptors 18, 19, 20. Additionally, netrin‐1 prevents ischemia and exerts anti‐inflammatory effects by binding to the adenosine receptor A2b 21…”
Section: Introductionmentioning
confidence: 99%